Rights of Foreign Workers in Vietnam - Hoi, Dao Xuan; Hai, Tran Dung (Journal of Ecohumanism, 2024)
This article provides a general overview of the rights of foreign workers, Vietnamese legal regulations on the rights of foreign workers, the current situation, and some solutions to improve the effectiveness of management and attract high-quality foreign workers.